Genetic association of intelligence with longevity in Drosophila melanogaster - Mousumee Khan; Enkhchimeg Lkhagva; Hae-mi Kim; Chongkai Zhai; Sharif Hasan Siddiqui; Seong-Tshool Hong (PLoS ONE, 2025)
Epidemiological studies in different populations, in different countries, and in different epochs consistently showed that high intelligence is positively correlated with longevity. The link between high intelligence and longevity has remained unknown, only to be assumed as a consequence of the socioeconomic difference associated with intelligence in human population. Here, we report that genome stability contributes both to lifespan and intelligence in Drosophila melanogaster. The intelligence of the genetically heterogenous flies was determined by T-maze olfactory memory assay, and the flies moving to the right direction defined as intelligent flies (INT) were separated from the flies moving to the wrong direction defined as non-intelligent flies (NINT). INT male and female lived 26.40% and 21.35% longer than NINT male and female, respectively, suggesting a possible genetic linkage between intelligence and longevity. The bidirectional selective breeding based on intelligence extended lifespans gradually generation by generation in INT breeding contrast to the reversed pattern in NINT breeding. INT of F12 generation lived longer than NINT of F12 generation, 63.91% for male and 67.88% for female, as a result from slower aging. The whole-genome transcriptome analysis showed the activation of the genes in ribosome and autophagy in INT and the pathways of genome stability and immune reaction in NINT. Especially, the genetic pathway associated with genome stability was most noticeable, indicating that genome stability contributes both to lifespan and intelligence in D. melanogaster.